Characterization of quantitative trait locus for days to heading in near-isogenic lines with genetic background of Indica-type rice variety IR64 (Oryza sativa) - Fujita, Daisuke; Santos, Rizza E.; Ebron, Leodegario A.; Fukuta, Yoshimichi; Kobayashi, Nobuya (Wiley, 2011)
With 3 figures and 3 tablesDays to heading (DTH) is considered as one of the most important traits for rice cultivation. A total of 334 introgression lines (ILs) of rice (Oryza sativa L.), with variation in agronomic traits in the genetic background of an Indica‐type variety, ‘IR64’, were developed and used in this study. Two ILs derived from ‘IR65600‐87‐2‐2‐3’ and ‘Hoshiaoba’ showed earlier heading than ‘IR64’, whereas two ILs from ‘IR65598‐112‐2’ and ‘IR69125‐25‐3‐1‐1’ showed later heading. To ascertain the genetic basis of four ILs, quantitative trait loci (QTL) analysis for DTH was conducted using F2 populations. Three QTLs for short DTH were detected on chromosome 8 in ‘IR65600‐87‐2‐2‐3’ and on chromosomes 6 and 11 in ‘Hoshiaoba’. Two QTLs for long DTH were detected on chromosome 6 in ‘IR65598‐112‐2’ and on chromosome 11 in ‘IR69125‐25‐3‐1‐1’. Three near‐isogenic lines (NILs) having a QTL from ‘IR65600‐87‐2‐2‐3’ and ‘Hoshiaoba’ were developed through marker‐assisted selection and they showed earlier heading than ‘IR64’, while two NILs from ‘IR65598‐112‐2’ and ‘IR69125‐25‐3‐1‐1’ showed later heading. These NILs for DTH are useful as research and breeding materials.